Learnings from development projects for organisational development - Kangasmäki, Jarkko (My University, 2015)
This study was done to examine how the case organisation utilises the knowledge gained from different technology and product development projects to learning in organisation and improving the way of working with future projects. In theoretical part the different knowledge types, knowledge management, learning in organisation, project management and project management maturity model is introduced. The study was done with qualitative survey (appendix 1) to evaluate how the case organisations experts, designers and managers evaluate their performance with development projects and where do they see the future development points for the organisation. In the end of this study the results of the questionnaire are evaluated towards the theo-ries presented and conclusions and recommendations are given based on them.
Keywords: Knowledge management; learning organisation; project management; project management maturity; development projects; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|